Reflection-AI: artificial intelligence or algorithmic instruction problem? Empowering students through situated knowledges-based reflexivity - Kim, Do Own (Donna) (Frontiers in Communication, 2025)
This article argues for a socio-technical rethinking of the contexts of teaching and assessing with artificial intelligence (AI), whether viewed as a threat or an opportunity. Drawing on technology studies and critical reflection on student experiences with English academic writing assignments in pre-AI era Korea, I reposition the “AI problem” as a cultural problem, namely an “algorithmic instruction” problem concerning structural prioritization of formulaic student work and pedagogical standardization, not a novel technology or individual moral(e) problem. Therefore, cultural, structural solutions are desirable. As potential breakthroughs, critical feminist epistemology of situated knowledges and qualitative methodological practice of reflexivity are discussed. Four practical mottos inspired from the concepts are introduced: 1. Building from positionality and reflexivity; 2. Memorization to (aided) storytelling; 3. “I” to “beyond-I” scaffolding; and 4. Evaluation to celebration. Examples from personal teaching experiences and implications for AI integration are discussed. Sustainable (re-)imaginations of AI in pedagogy are recommended.